Epistemology of Islamic Modern Education in the Thought of KH ABDURROHIM - Muntaha Mahfud; Rohmad Rohmad; Fauzi Fauzi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe: (1) The background of K. H Abdurrohim's life, which influenced his thinking in the field of Islamic education. (2) Thought Etymology, K. H Abdurrohim, on modern Islamic education. (3) The role of K. H Abdurrohim in the development of Islamic educational institutions (4) The impact of K. H Abdurrohim's thoughts on the development of Islamic education.The research was conducted using historical research methods to be able to reconstruct historical events at a certain period. The historical method is used by going through several stages consisting of heuristics, verification, interpretation, and historiography. Sources of data in the study consisted of primary and secondary sources. The primary sources used are the results of interviews with the closest figures and documents related to the educational institutions he founded. The secondary sources used are books and journals that are related to the research topic.Based on the results of the research, it is shown that: (1) Educational, family, social, and economic background influence his thinking in developing Islamic educational institutions. (2) The role of K. H Abdurrohim in the development of modern Islamic education can be seen from the idea of establishing a formal educational institution under the foundation of a boarding school. (3) K. H Abdurrohim's thoughts on the modernization of Islamic educational institutions gave birth to a millennial generation with Ahlusuna Waljamaah's perspective.